Potential antiproliferative effect of isoxazolo- and thiazolo coumarin derivatives on breast cancer mediated bone and lung metastases - Ballazhi Lulzime; Popovski Emil; Jashari Ahmed; Imeri Faik; Ibrahimi Ibrahim; Mikhova Bozhana; Mladenovska Kristina (Acta Pharmaceutica)
The study highlights the current progress in the development of coumarin scaffolds for drug discovery as novel anticancer agents in metastatic breast cancer. Eight compounds, combining the coumarin core and five membered heterocycles (isoxazoles and thiazoles) in hydrazinyldiene- -chroman-2,4-diones, were characterized in terms of a potential antiproliferative effect on bone (SCP1833) and lung (SCP4175) metastatic breast cancer cell lines using the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide assay. Cell viability was evaluated after 48 and 72 h of treatment and the 50 % inhibitory concentrations were determined. The results demonstrated dose- and time-dependent activity, with the most potent molecules having a thiazole moiety, without or with additional methyl group(s) attached to the carbon(s) at position(s) 5 and/or 4 in the thiazole ring. These molecules possessed significantly higher potency against both test cell lines compared to 4-hydroxycoumarin